Angst vor der Landschaft.: Ein wissenschaftlicher Essay - Eisel, Ulrich (ERDKUNDE, 2001)
1. The idea of landscape constitutes its perception. This idea, effective in modern time, came into being in the paintings of the Renaissance. Landscape is an object which is transmitted aesthetically. This circumstance is verified by its perception as kitschy for modern consciousness. Whenever something is considered to be Kitsch, it points to art. Realistic painting is suggested to be Kitsch, when it is atmospheric, as well as when it is banal documentalism; the paradigm of Kitsch is the holiday snapshot of the landscape. 2. The aesthetic sensitiveness is the modern form of erotic ecstasy in ritual sacral acts. Landscape brings back memory to erotic and sacred emotions, because it has as an idea an aesthetical effect. 3. The Kitsch suspicion shall counter-caricature the potential confession to this level of experience. The anxiety of the holiday snapshot is the paradox anxiousness of, on the one hand to confess feelings, which are shameful for a modern human being, and on the other hand, not to be equipped with a level of personal charisma and attractive power, namely erotics, which is embodied in the denied feelings.